Positive electrode for lithium-sulfur battery, method for producing same and lithium-sulfur battery including same
By using a porous carbon material with a particle size of less than 10 μm, produced through centrifugation, the positive electrode for lithium-sulfur batteries maintains porosity and reactivity, addressing the issue of reduced discharge capacity and energy density caused by fine powders.
Patent Information
- Application Number
- JP2024555422
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-11-14
- Filing Date
- 2023-11-14
- Publication Date
- 2025-04-16
- Estimated Expiration
- 2043-11-14
AI Technical Summary
The particle size of carbon materials in sulfur-carbon composites for lithium-sulfur batteries affects the porosity and reactivity of the positive electrode, leading to reduced discharge capacity and energy density when fine powders are present.
A positive electrode for lithium-sulfur batteries is developed using a porous carbon material with a particle size (D10 standard) of less than 10 μm, produced by centrifugation, which ensures porosity and maintains reactivity even with fine powders.
The approach ensures that the porosity of the positive electrode is maintained, preventing a decrease in discharge capacity and energy density, and allowing the lithium-sulfur battery to perform at levels comparable to those without fine powders.
Smart Images

Figure 2025511554000001 
Figure 2025511554000002 
Figure 2025511554000003
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0151291 dated November 14, 2022 and Korean Patent Application No. 10-2023-0156911 dated November 14, 2023, and incorporates all contents disclosed in the documents of said Korean patent applications as part of this specification.
[0002] The present invention relates to a positive electrode for a lithium-sulfur battery, a method for producing the same, and a lithium-sulfur battery including the same. [Background technology]
[0003] Recently, interest in energy storage technology has been on the rise. Its application areas have expanded to include mobile phones, video cameras, laptops, and even the energy of electric vehicles, and efforts in the research and development of electrochemical devices have become more and more concrete.
[0004] Electrochemical elements are the field that has attracted the most attention in this regard, and among them, the development of secondary batteries that can be charged and discharged has become a focus of attention. Recently, in developing such batteries, research and development has been conducted on new electrode and battery designs to improve capacity density and energy efficiency.
[0005] Among the secondary batteries currently in use, lithium secondary batteries, developed in the early 1990s, have been attracting attention due to their advantages of higher operating voltage and significantly higher energy density compared to conventional batteries that use aqueous electrolytes, such as Ni-MH, Ni-Cd, and sulfuric acid-lead batteries.
[0006] In particular, the lithium-sulfur (Li-S) battery is a secondary battery that uses a sulfur-based material with a S-S bond (Sulfur-Sulfur bond) as the positive electrode active material and lithium metal as the negative electrode active material. Sulfur, the main material of the positive electrode active material, has the advantages of being very abundant, non-toxic, and low weight per atom. In addition, the theoretical discharge capacity of the lithium-sulfur battery is 1675mAh / g-sulfur, and the theoretical energy density is 2,600Wh / kg, which is much higher than the theoretical energy density of other battery systems currently being researched (Ni-MH battery: 450Wh / kg, Li-FeS battery: 480Wh / kg, Li-MnO2 battery: 1,000Wh / kg, Na-S battery: 800Wh / kg), making it the most promising battery currently being developed.
[0007] During the discharge reaction of a lithium-sulfur battery, an oxidation reaction of lithium occurs at the negative electrode, and a reduction reaction of sulfur occurs at the positive electrode. Before discharge, sulfur has a cyclic S8 structure, but during the reduction reaction (discharge), the S-S bond is broken, decreasing the oxidation number of S, and during the oxidation reaction (charge), the S-S bond is formed again, increasing the oxidation number of S. Electrical energy is stored and generated through an oxidation-reduction reaction. During this reaction, sulfur is reduced from the cyclic S8 to a linear lithium polysulfide (Li2S x , x = 8, 6, 4, 2), and finally when these lithium polysulfides are completely reduced, lithium sulfide (Li2S) is generated. Due to the process of reduction to each lithium polysulfide, the discharge behavior of lithium-sulfur batteries is different from that of lithium-ion batteries, and is characterized by a stepwise discharge voltage.
[0008] In order to improve the performance of such lithium-sulfur batteries, it is necessary to maximize the reactivity of the positive electrode active material. Since sulfur used as a positive electrode active material of lithium-sulfur batteries has no conductivity, a carbon material is used as a carrier to maximize the reactivity, and a sulfur-carbon composite in which the carbon material and sulfur are mixed is mainly used.
[0009] In the sulfur-carbon composite, when a carbon material having a high specific surface area and porosity is mixed with sulfur, the amount of sulfur supported can be increased, and the energy density of the lithium-sulfur battery can be improved. However, there is a problem that the reactivity is decreased, resulting in a decrease in discharge capacity, which needs to be improved.
[0010] The particle size of the carbon material is a factor that has a large effect on the discharge capacity and energy density of a lithium-sulfur battery, and when the carbon material contains fine powder, the porosity of the positive electrode cannot be ensured, resulting in a problem of reduced reactivity of the lithium-sulfur battery. Therefore, a carbon material that does not contain fine powder must be used, but it is not easy to control the fine powder because the density of the carbon material is low. Therefore, research is needed to ensure that the discharge capacity and energy density of a lithium-sulfur battery are not reduced even when the carbon material contains fine powder. [Prior art documents] [Patent documents]
[0011] [Patent Document 1] Korean Patent Publication No. 10-2020-0109861 Summary of the Invention [Problem to be solved by the invention]
[0012] In order to solve the above problems, the present inventors have conducted extensive research and found that when a porous carbon material having a particle size (D10 standard) of less than 10 μm produced by centrifugal grinding is used as a carbon material for a sulfur-carbon composite, which is a positive electrode active material, the porosity of the positive electrode can be ensured even if the particle size (D10 standard) of the porous carbon material is less than 10 μm, thereby improving the discharge capacity and reactivity of a lithium-sulfur battery and ensuring the energy density, thereby completing the present invention.
[0013] Therefore, an object of the present invention is to provide a positive electrode for a lithium-sulfur battery in which the discharge capacity and energy density of the lithium-sulfur battery are not reduced even when the particle size (D10 standard) of the porous carbon material is less than 10 μm.
[0014] Another object of the present invention is to provide a method for manufacturing the positive electrode for a lithium-sulfur battery and a lithium-sulfur battery including the same. [Means for solving the problem]
[0015] In order to achieve the above objective, The present invention relates to a current collector; and a positive electrode active material layer disposed on at least one surface of the current collector; The positive electrode active material layer includes, as a positive electrode active material, a porous carbon material and a sulfur-carbon composite containing sulfur in at least a part of the inside and the outside surface of the porous carbon material, The particle size (D10 standard) of the porous carbon material is less than 10 μm; The present invention provides a positive electrode for a lithium-sulfur battery, wherein the positive electrode has a porosity of more than 75% and not more than 85%.
[0016] The present invention also provides a method for producing a porous carbon material having a particle size (D10 standard) of less than 10 μm by: (1) centrifugal crushing a porous carbon material; (2) mixing the porous carbon material with sulfur and heat treating the mixture to prepare a sulfur-carbon composite; (3) preparing a positive electrode slurry containing the sulfur-carbon composite; and (4) applying the positive electrode slurry to a current collector.
[0017] The present invention also provides a lithium-sulfur battery comprising the positive electrode of the present invention; a negative electrode; a separator interposed between the positive electrode and the negative electrode; and an electrolyte. Effect of the Invention
[0018] If the particle size (D10) of the porous carbon material of the sulfur-carbon composite is less than 10 μm, the carbon material blocks the pores of the positive electrode, reducing the porosity of the positive electrode, which in turn reduces the reactivity, discharge capacity, and energy density of the lithium-sulfur battery.
[0019] In the positive electrode for a lithium-sulfur battery of the present invention, even if the particle size (D10) of the porous carbon material of the sulfur-carbon composite, which is the positive electrode active material, is less than 10 μm, the tap density of the carbon material is low, the pores of the positive electrode are not blocked, and the porosity of the positive electrode can be ensured. Therefore, even if the particle size (D10) of the porous carbon material is less than 10 μm, the energy density of the lithium-sulfur battery is prevented from decreasing and the reactivity of the lithium-sulfur battery can be ensured. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present invention will now be described in more detail.
[0021] The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept that is consistent with the technical idea of the present invention, based on the principle that the inventor can appropriately define the concept of the term in order to best describe his / her invention.
[0022] The term "composite" as used herein means a material in which two or more materials are combined to form physically and chemically distinct phases, thereby exhibiting a more effective function.
[0023] Lithium-sulfur batteries use sulfur as the positive electrode active material and lithium metal as the negative electrode active material. When a lithium-sulfur battery is discharged, an oxidation reaction of lithium occurs at the negative electrode, and a reduction reaction of sulfur occurs at the positive electrode. At this time, the reduced sulfur combines with lithium ions transferred from the negative electrode and is converted into lithium polysulfide, which ultimately leads to a reaction that forms lithium sulfide.
[0024] Lithium-sulfur batteries have attracted attention as a next-generation battery due to their significantly higher theoretical energy density than conventional lithium secondary batteries, and because sulfur, which is used as the positive electrode active material, is abundant and inexpensive, they can reduce the unit cost of battery production.
[0025] Despite these advantages, it is difficult to realize all of the theoretical energy density in actual operation due to the low electrical conductivity and lithium ion conductivity of sulfur, which is the positive electrode active material.
[0026] In order to improve the electrical conductivity of sulfur, a sulfur-carbon composite containing sulfur in at least a part of the inner and outer surfaces of the porous carbon material is most commonly used as a positive electrode active material for lithium-sulfur batteries. However, the discharge capacity and energy density of the lithium-sulfur battery are affected by the particle size of the porous carbon material. The more fine powder the porous carbon material contains, the more the fine powder packs the pores of the positive electrode, and the reaction that causes the discharge capacity does not proceed quickly, resulting in a decrease in the reactivity of the lithium-sulfur battery. Therefore, it is necessary to adjust the fine powder of the porous carbon material in the sulfur-carbon composite, but the porous carbon material has a low density, so that it is difficult to adjust the fine powder.
[0027] Therefore, the present invention aims to provide a positive electrode for a lithium-sulfur battery that can ensure the porosity of the positive electrode by not blocking the pores of the positive electrode even if the porous carbon material contains fine powder.
[0028] In the present invention, the fine powder may mean a powder having a particle size (D10 standard) of less than 10 μm.
[0029] Positive electrode for lithium-sulfur batteries The present invention relates to a current collector; and a positive electrode active material layer disposed on at least one surface of the current collector; The positive electrode active material layer includes, as a positive electrode active material, a porous carbon material and a sulfur-carbon composite containing sulfur in at least a part of the inside and the outside surface of the porous carbon material, The particle size (D10 standard) of the porous carbon material is less than 10 μm, The positive electrode for a lithium-sulfur battery has a porosity of more than 75% and not more than 85%.
[0030] The current collector is not particularly limited as long as it supports the positive electrode active material, does not cause chemical changes in the battery, and has high conductivity. For example, copper, stainless steel, aluminum, nickel, titanium, palladium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, silver, etc., aluminum-cadmium alloy, etc. may be used.
[0031] The positive electrode current collector may have fine irregularities on its surface to strengthen the bonding force with the positive electrode active material, and may be in various forms such as a film, sheet, foil, mesh, net, porous body, foam, nonwoven fabric, etc.
[0032] The positive electrode active material layer is disposed on at least one surface of a current collector, and may include, as a positive electrode active material, a porous carbon material and a sulfur-carbon composite containing sulfur in at least a part of an inner surface and an outer surface of the porous carbon material.
[0033] The sulfur may be inorganic sulfur (S8), Li-S n (n≧1), organic sulfur compounds and carbon-sulfur polymers [(C2S x ) n, x=2.5 to 50, n≧2]. Preferably, inorganic sulfur (S8) may be used.
[0034] In addition, the sulfur may be located not only inside the pores of the porous carbon material but also on the surface, and in this case, it may be present in an area of less than 100%, preferably 1 to 95%, and more preferably 60 to 90% of the entire surface of the porous carbon material. When the sulfur is present on the surface of the porous carbon material within the above range, it can exhibit the maximum effect in terms of the electron transfer area and the wettability of the electrolyte. Specifically, since the sulfur is impregnated thinly and uniformly on the surface of the porous carbon material in the above range, it is possible to increase the contact area of electron transfer during charging and discharging. If the sulfur is located on 100% of the surface area of the porous carbon material, the porous carbon material is completely covered with sulfur, which reduces the wettability of the electrolyte and reduces the contact with the conductive material contained in the electrode, making it unable to receive electron transfer and unable to participate in the reaction.
[0035] The porous carbon material can generally be prepared by carbonizing various carbon precursors. The porous carbon material contains non-uniform pores, the average diameter of the pores being in the range of 1-200 nm, and the porosity or void ratio may be in the range of 10-90% of the total volume of the porous carbon material. If the average diameter of the pores is less than the range, the pore size is merely at the molecular level, making it impossible to impregnate with sulfur, and conversely, if it exceeds the range, the mechanical strength of the porous carbon material is weakened, making it unsuitable for application to the manufacturing process of an electrode.
[0036] The shape of the porous carbon material may be spherical, rod-like, needle-like, plate-like, tubular or bulk, and any shape that is commonly used in lithium-sulfur batteries may be used without limitation.
[0037] The porous carbon material may be any material commonly used in the art that has a porous structure or a high specific surface area. For example, the porous carbon material may be at least one selected from the group consisting of graphite, graphene, carbon black such as denka black, acetylene black, ketjen black, channel black, furnace black, lamp black, and thermal black, carbon nanotubes (CNTs) such as single-walled carbon nanotubes (SWCNTs) and multi-walled carbon nanotubes (MWCNTs), carbon fibers such as graphite nanofibers (GNFs), carbon nanofibers (CNFs), and activated carbon fibers (ACFs), graphite such as natural graphite, artificial graphite, and expanded graphite, and activated carbon, but is not limited thereto. Preferably, the porous carbon material may be carbon nanotubes.
[0038] In the present invention, the particle size (D10 standard) of the porous carbon material of the sulfur-carbon composite may be a fine powder of less than 10 μm. Conventionally, when the porous carbon material of the sulfur-carbon composite contains fine powder, the fine powder blocks the pores of the positive electrode, reducing the porosity of the positive electrode, making it difficult to ensure the reactivity of the lithium-sulfur battery, and there is a problem that the discharge capacity and energy density are reduced. That is, the discharge capacity and energy density of the lithium-sulfur battery are affected by the particle size of the porous carbon material. In the present invention, even if the particle size (D10 standard) of the porous carbon material is fine powder of less than 10 μm, the porosity of the positive electrode can be ensured, so that the lithium-sulfur battery can have a discharge capacity, energy density, and reactivity at the same level as a lithium-sulfur battery containing a porous carbon material that does not contain fine powder. Therefore, the positive electrode for a lithium-sulfur battery of the present invention and the lithium-sulfur battery including the same are not affected by the particle size of the porous carbon material, and therefore there is no need to adjust the particle size of the porous carbon material.
[0039] The porous carbon material having a particle size (based on D10) of less than 10 μm may be manufactured by centrifugal pulverization. The centrifugal pulverization may be a process in which large particles are pulverized by colliding with the blades of a centrifugal pulverizer to produce particles with a small particle size. For example, carbon nanotube particles having a plurality of carbon nanotube chains entangled with each other may be pulverized into particles with a small particle size by breaking the cavities in which the carbon nanotubes are entangled with each other by the blades of the pulverizer. At this time, the degree of entanglement is reduced by breaking the plurality of entangled carbon nanotube chains, so that a low tap density can be exhibited. Specifically, the tap density of the porous carbon material having a particle size (based on D10) of less than 10 μm manufactured by the centrifugal pulverization may be 0.01 to 0.1 g / cc, preferably 0.03 to 0.07 g / cc. Therefore, even if the particle size (based on D10) of the porous carbon material is less than 10 μm, the positive electrode can have high porosity. However, the tap density of porous carbon materials not produced by centrifugal grinding and having a particle size (D10 standard) of less than 10 μm exceeds 0.1 g / cc, and the high tap density may clog the pores of the positive electrode, making it impossible to provide a positive electrode with high porosity, and the reactivity of the lithium-sulfur battery may decrease.
[0040] The sulfur-carbon composite may contain 70 to 90 wt %, preferably 70 to 85 wt %, and more preferably 72 to 80 wt %, of sulfur based on 100 wt % of the sulfur-carbon composite. If the sulfur content is less than the above range, the content of the porous carbon material in the sulfur-carbon composite is relatively high, so that the specific surface area increases and the binder content increases during the preparation of the positive electrode. Such an increase in the amount of binder used may ultimately increase the sheet resistance of the positive electrode and act as an insulator that hinders electron pass, thereby deteriorating the performance of the battery. On the other hand, if the sulfur content exceeds the above range, the sulfur that cannot be bonded to the porous carbon material may aggregate with each other or be re-eluted on the surface of the porous carbon material, making it difficult to receive electrons and unable to participate in the electrochemical reaction, which may cause a loss of capacity in the battery.
[0041] The positive electrode active material may be contained in an amount of 70 to 95 wt%, preferably 75 to 90 wt%, more preferably 80 to 90 wt%, based on the total weight of the positive electrode active material layer. If the positive electrode active material is contained in an amount less than 70 wt%, the battery performance may be deteriorated, and if it exceeds 95 wt%, the content of conductive material and binder other than the positive electrode active material is relatively reduced, and properties such as conductivity, durability, and securing of lithium ion transport paths may be deteriorated.
[0042] In addition, the sulfur may be contained in an amount of 65 to 80 wt%, preferably 67 to 75 wt%, based on the total weight of the positive electrode active material layer. If the sulfur content is less than 65 wt%, the positive electrode active material is insufficient, making it impossible to ensure the energy density of the lithium-sulfur battery, and if it exceeds 80 wt%, the content of the conductive material and binder is relatively reduced, which may result in a decrease in properties such as conductivity, durability, and securing of lithium ion transport paths.
[0043] The positive electrode active material layer may further contain a conductive material or a binder.
[0044] The conductive material is a material that electrically connects the electrolyte and the positive electrode active material and serves as a path through which electrons move from a current collector to the positive electrode active material. Any material that does not undergo chemical change in a lithium-sulfur battery and has porosity and conductivity may be used without limitation.
[0045] For example, the conductive material may be a carbon-based material having porosity, and examples of such carbon-based materials include carbon black (CB), graphite, graphene, activated carbon, carbon nanotubes (CNT), carbon fibers, metallic fibers such as metal meshes, metallic powders such as copper, silver, nickel, and aluminum, and organic conductive materials such as polyphenylene derivatives. The conductive materials may be used alone or in combination.
[0046] Currently, commercially available conductive materials include acetylene black (Chevron Chemical Company and Gulf Oil Company products, etc.), Ketjen Black EC (Armak Company product), Vulcan XC-72 (Cabot Company product), and Super P (MMM Company product), etc. Examples include acetylene black, carbon black, and graphite.
[0047] The conductive material may be contained in an amount of 1 to 20 wt%, preferably 3 to 18 wt%, more preferably 5 to 15 wt%, based on the total weight of the positive electrode active material layer. If the conductive material is contained in an amount less than 1 wt%, the conductivity of the positive electrode cannot be ensured, and if it is contained in an amount exceeding 20 wt%, the contents of the positive electrode active material and binder are relatively reduced, which may result in a decrease in battery performance.
[0048] The binder serves to hold the positive electrode active material on the positive electrode current collector and to connect the positive electrode active materials. The binder may include, for example, one or more selected from the group consisting of styrene-butadiene rubber, carboxymethyl cellulose, poly(vinyl acetate), polyvinyl alcohol, polyethylene oxide, polyvinylpyrrolidone, alkylated polyethylene oxide, crosslinked polyethylene oxide, polyvinyl ether, poly(methyl methacrylate), polyvinylidene fluoride, copolymer of polyhexafluoropropylene and polyvinylidene fluoride (trade name: Kynar), poly(ethyl acrylate), polytetrafluoroethylene, polyvinyl chloride, polyacrylonitrile, polyvinylpyridine, polystyrene, polyacrylic acid, derivatives thereof, blends thereof, and copolymers thereof.
[0049] The binder may be contained in an amount of 1 to 20 wt%, preferably 3 to 18 wt%, more preferably 5 to 15 wt%, based on the total weight of the positive electrode active material layer. If the binder is contained in an amount less than 1 wt%, the bonding strength between the positive electrode active materials or between the positive electrode active material and the current collector may be significantly reduced, and if the binder is contained in an amount more than 20 wt%, the capacity of the battery may be reduced.
[0050] The porosity of the positive electrode for lithium-sulfur batteries of the present invention may be more than 75% and not more than 85%. That is, the positive electrode for lithium-sulfur batteries of the present invention may have a porosity of more than 75% and not more than 85% even if the particle size (D10 standard) of the porous carbon material of the sulfur-carbon composite is less than 10 μm. Therefore, a lithium-sulfur battery including the same does not show a decrease in reactivity and can maintain its reactivity.
[0051] If the porosity of the positive electrode is 75% or less, the pores are insufficient, and therefore a lithium-sulfur battery having excellent reactivity cannot be provided, and if the porosity of the positive electrode is more than 85%, there is a limit to the increase in energy density of the lithium-sulfur battery. In addition, the electrolyte may not be present in all of the pores of the positive electrode, and some pores of the positive electrode may not be utilized in the reaction, which may result in a loss of the positive electrode active material.
[0052] Method for manufacturing positive electrodes for lithium-sulfur batteries The present invention also relates to a method for producing a positive electrode for a lithium-sulfur battery, the method comprising the steps of: (1) centrifugal crushing a porous carbon material to produce a porous carbon material having a particle size (D10 standard) of less than 10 μm; (2) mixing the porous carbon material with sulfur and heat treating the mixture to prepare a sulfur-carbon composite; (3) preparing a positive electrode slurry containing the sulfur-carbon composite; and (4) applying the positive electrode slurry to a current collector.
[0053] The step (1) is a step of producing a porous carbon material having a particle size (D10 standard) of less than 10 μm by centrifugal pulverization of the porous carbon material.
[0054] The porous carbon material is as described above.
[0055] The centrifugal grinding may be carried out at 6000 to 18000 rpm and a linear velocity of 80 to 200 m / s, and preferably at 6000 to 18000 rpm and a linear velocity of 90 to 160 m / s.
[0056] Specifically, the centrifugal grinding may include centrifugally grinding the porous carbon material at the rpm and linear velocity, and then adjusting the mesh size of a sieve in the centrifugal grinder to adjust the particle size of the porous carbon material. In addition, a cyclone process may be performed to capture the porous carbon material that has passed through the sieve, thereby adjusting the particle size of the porous carbon material. The porous carbon material obtained through the process may have a particle size (D10 standard) of less than 10 μm.
[0057] As described above, by pulverizing the porous carbon material through the centrifugal pulverization, the porous carbon material having a particle size (based on D10) of less than 10 μm can have a low tap density. Specifically, the tap density of the porous carbon material may be 0.01 to 0.1 g / cc, preferably 0.03 to 0.07 g / cc. On the other hand, when the porous carbon material is not manufactured by centrifugal pulverization, the tap density may exceed 0.1 g / cc even if the particle size (based on D10) of the porous carbon material is less than 10 μm. Therefore, the positive electrode for the lithium-sulfur battery of the present invention can have high porosity even if the particle size (based on D10) of the porous carbon material is less than 10 μm. On the other hand, the porous carbon material not manufactured by centrifugal pulverization can block the pores of the positive electrode due to its high tap density, so that a positive electrode having high porosity cannot be manufactured.
[0058] The step (2) is a step of mixing the porous carbon material with sulfur and heat-treating the mixture to produce a sulfur-carbon composite.
[0059] The porous carbon material having a particle size (D10 standard) of less than 10 μm produced in the step (1) is mixed with sulfur, and the mixing may be simple mixing.
[0060] The heat treatment may be performed at a temperature of 130°C to 170°C, and the heat treatment time is not particularly limited, but may be performed for 15 minutes to 2 hours. If the temperature exceeds 170°C, there is a problem that sulfur vaporizes, and if it is less than 130°C, there is a problem that sulfur does not melt and is not uniformly distributed. If the heat treatment time is less than 15 minutes, there is a problem that sulfur is not sufficiently dissolved and impregnated, and if it exceeds 2 hours, there is a problem that some sulfur vaporizes or is impregnated unevenly.
[0061] The step (3) is a step of producing a positive electrode slurry containing the sulfur-carbon composite produced in the step (2).
[0062] The positive electrode slurry may form a positive electrode active material layer. The positive electrode slurry may include a sulfur-carbon composite as a positive electrode active material, and may further include a binder or a conductive material. The binder and the conductive material are as described above.
[0063] The positive electrode slurry may also contain a solvent to uniformly disperse the sulfur-carbon composite. As such a solvent, water is most preferable as an aqueous solvent, and in this case, the water may be distilled water or deionized water. However, the solvent is not necessarily limited to these, and a lower alcohol that is easily mixed with water may be used as needed. The lower alcohol may be methanol, ethanol, propanol, isopropanol, butanol, etc., and these may be preferably mixed with water.
[0064] The content of the solvent may be at a level that allows the positive electrode slurry to be easily applied to the current collector, and the specific content varies depending on the application method and device.
[0065] The positive electrode slurry may further include, as necessary, a substance commonly used in the art for the purpose of improving its function, etc., such as a viscosity modifier, a fluidizing agent, a filler, etc.
[0066] The step (4) is a step of applying the positive electrode slurry prepared in the step (3) onto a current collector.
[0067] The method of applying the positive electrode slurry to the current collector is not particularly limited in the present invention, and examples of the method include doctor blade, die casting, comma coating, screen printing, etc. In addition, the positive electrode slurry may be applied to the current collector by molding on a separate substrate and then pressing or lamination.
[0068] After the step (4), a drying step may be performed to remove the solvent from the positive electrode slurry. The drying step is performed at a temperature and time level that can sufficiently remove the solvent, and the conditions vary depending on the type of solvent, and are not particularly limited in the present invention. Examples include drying with warm air, hot air, or low-humidity air, vacuum drying, and drying by irradiation with (far) infrared rays and electron beams. The drying speed is usually adjusted so that the solvent can be removed as quickly as possible within a speed range that does not cause cracks in the positive electrode active material layer due to stress concentration or peeling off of the positive electrode active material layer from the positive electrode current collector.
[0069] Furthermore, after the drying, the current collector can be pressed to increase the density of the positive electrode active material in the positive electrode. Examples of the pressing method include die pressing and roll pressing.
[0070] The porosity of the positive electrode for lithium-sulfur batteries manufactured by the above manufacturing method may be more than 75% and not more than 85%. In general, if the porous carbon material is a fine powder having a particle size (based on D10) of less than 10 μm, the fine powder of the porous carbon material blocks the pores of the positive electrode, making it impossible to manufacture a positive electrode with high porosity. This causes a problem of reduced reactivity of the lithium-sulfur battery. However, in the present invention, by centrifugal pulverization of the porous carbon material in the above step (1), it is possible to manufacture a positive electrode for lithium-sulfur batteries with a porosity of more than 75% and not more than 85%, even if the porous carbon material has a particle size (based on D10) of less than 10 μm.
[0071] Therefore, the present invention can provide a method for manufacturing a positive electrode for a lithium-sulfur battery in which the porosity of the positive electrode is not affected by fine powder of a porous carbon material.
[0072] Lithium-sulfur battery The present invention relates to a lithium-sulfur battery that includes a positive electrode; a negative electrode; a separator interposed between the positive electrode and the negative electrode; and an electrolyte.
[0073] The positive electrode may be the positive electrode for a lithium-sulfur battery of the present invention described above.
[0074] The negative electrode may include a current collector and a negative electrode active material layer coated on one or both sides of the current collector, or the negative electrode may be a lithium metal plate.
[0075] The current collector is for supporting the negative electrode active material layer, and is the same as that described for the current collector used in the positive electrode.
[0076] The negative electrode active material layer may include, in addition to the negative electrode active material, a conductive material, a binder, etc. In this case, the conductive material and the binder are as described above.
[0077] The negative electrode active material is a lithium ion (Li + The lithium-containing compound may include a material capable of reversible intercalation or deintercalation of lithium ions, a material capable of reversibly reacting with lithium ions to form a lithium-containing compound, lithium metal, or a lithium alloy.
[0078] The lithium ion (Li + The material capable of reversibly inserting or de-inserting lithium ions (Li) may be, for example, crystalline carbon, amorphous carbon, or a mixture thereof. + The material capable of reacting with lithium to reversibly form a lithium-containing compound may be, for example, tin oxide, titanate, or silicon. The lithium alloy may be, for example, an alloy of lithium (Li) and a metal selected from the group consisting of sodium (Na), potassium (K), rubidium (Rb), cesium (Cs), francium (Fr), beryllium (Be), magnesium (Mg), calcium (Ca), strontium (Sr), barium (Ba), radium (Ra), aluminum (Al), and tin (Sn).
[0079] Preferably, the negative electrode active material is lithium metal, and more particularly, may be in the form of a lithium metal thin film or lithium metal powder.
[0080] A separator may be interposed between the positive electrode and the negative electrode.
[0081] The separator separates or insulates the positive electrode and the negative electrode from each other and enables lithium ion transport between the positive electrode and the negative electrode, and may be made of a porous non-conductive or insulating material. Any material that is generally used as a separator in a lithium secondary battery may be used without any particular limitation. Such a separator may be an independent member such as a film, or may be a coating layer added to the positive electrode and / or the negative electrode.
[0082] The separation membrane is preferably one that has low resistance to the ion movement of the electrolyte and has excellent moisture-absorbing ability for the electrolyte.
[0083] The separator may be made of a porous substrate. The porous substrate may be any porous substrate typically used in secondary batteries. A porous polymer film may be used alone or in combination. For example, a nonwoven fabric such as a high melting point glass fiber or polyethylene terephthalate fiber, or a polyolefin-based porous membrane may be used, but is not limited thereto.
[0084] The material of the porous substrate is not particularly limited in the present invention, and any porous substrate that is generally used in electrochemical elements may be used. For example, the porous substrate may be made of a material selected from the group consisting of polyolefins such as polyethylene and polypropylene, polyesters such as polyethyleneterephthalate and polybutyleneterephthalate, polyamides, polyacetals, polycarbonates, polyimides, polyetheretherketones, polyethersulfones, polyphenyleneoxides, polyphenylenesulfides, polyethylenenaphthalate, polytetrafluoroethylene, polyvinylidenefluoride, polyvinyl chloride, polyacrylonitrile, cellulose, nylon, poly(p-phenylene benzobisoxazole), and the like. The insulating layer may include one or more materials selected from the group consisting of benzobisoxazole and polyarylate.
[0085] The thickness of the porous substrate is not particularly limited, but may be 1 to 100 μm, preferably 5 to 50 μm. The thickness of the porous substrate is not limited to the above range, but if the thickness is too thin below the lower limit, the mechanical properties may be deteriorated and the separator may be easily damaged during use of the battery.
[0086] The average diameter and porosity of the pores present in the porous substrate are not particularly limited, and may be 0.001 to 50 μm and 10 to 95%, respectively.
[0087] The electrolyte contains lithium ions and serves to cause an electrochemical oxidation or reduction reaction between the positive electrode and the negative electrode through the medium of lithium ions.
[0088] The electrolyte can be a non-aqueous liquid electrolyte or a solid electrolyte that does not react with lithium metal, but is preferably a non-aqueous electrolyte that includes an electrolyte salt and an organic solvent.
[0089] The electrolyte salt contained in the non-aqueous electrolyte is a lithium salt. The lithium salt may be any salt that is commonly used in electrolytes for lithium secondary batteries. For example, LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 , LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, CH3SO3Li, (CF3SO2)2NLi, LiN(SO2F)2, lithium chloroborane, lithium lower aliphatic carbon acids, lithium 4-phenylborate, lithium imide, etc. may also be used.
[0090] The concentration of the lithium salt may be 0.2-2M, specifically 0.4-2M, more specifically 0.4-1.7M, depending on various factors such as the exact composition of the electrolyte solvent mixture, the solubility of the salt, the conductivity of the dissolved salt, the charge and discharge conditions of the battery, the operating temperature, and other factors known in the lithium battery art. If the lithium salt is used at a concentration less than 0.2M, the conductivity of the electrolyte may decrease and the performance of the electrolyte may decrease, and if the concentration exceeds 2M, the viscosity of the electrolyte may increase and the mobility of the lithium ions may decrease.
[0091] The organic solvent contained in the nonaqueous electrolyte may be any organic solvent that is commonly used in electrolytes for lithium secondary batteries, and may be, for example, ethers, esters, amides, linear carbonates, cyclic carbonates, etc., each of which may be used alone or in combination of two or more. Among these, a representative example may include an ether-based compound.
[0092] The ether-based compound may include acyclic ethers and cyclic ethers.
[0093] For example, the acyclic ether may be one or more selected from the group consisting of dimethyl ether, diethyl ether, dipropyl ether, methyl ethyl ether, methyl propyl ether, ethyl propyl ether, dimethoxyethane, diethoxyethane, ethylene glycol ethyl methyl ether, diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol methyl ethyl ether, triethylene glycol dimethyl ether, triethylene glycol diethyl ether, triethylene glycol methyl ethyl ether, tetraethylene glycol dimethyl ether, tetraethylene glycol diethyl ether, tetraethylene glycol methyl ethyl ether, polyethylene glycol dimethyl ether, polyethylene glycol diethyl ether, and polyethylene glycol methyl ethyl ether, but is not limited thereto.
[0094] For example, the cyclic ether may be one or more selected from the group consisting of 1,3-dioxolane, 4,5-dimethyl-dioxolane, 4,5-diethyl-dioxolane, 4-methyl-1,3-dioxolane, 4-ethyl-1,3-dioxolane, tetrahydrofuran, 2-methylfuran, 2-methyltetrahydrofuran, 2,5-dimethyltetrahydrofuran, 2,5-dimethoxytetrahydrofuran, 2-ethoxytetrahydrofuran, 2-methyl-1,3-dioxolane, 2-vinyl-1,3-dioxolane, 2,2-dimethyl-1,3-dioxolane, 2-methoxy-1,3-dioxolane, 2-ethyl-2-methyl-1,3-dioxolane, tetrahydropyran, 1,4-dioxane, 1,2-dimethoxybenzene, 1,3-dimethoxybenzene, 1,4-dimethoxybenzene, and isosorbide dimethyl ether, but is not limited thereto.
[0095] The ester in the organic solvent may be any one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone, or a mixture of two or more thereof, but is not limited thereto.
[0096] Specific examples of the linear carbonate compound include, but are not limited to, any one selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, and ethyl propyl carbonate, or a mixture of two or more of these.
[0097] Specific examples of the cyclic carbonate compound include any one or mixtures of two or more selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, vinylene carbonate, vinylethylene carbonate, and halides thereof. Examples of halides thereof include, but are not limited to, fluoroethylene carbonate (FEC).
[0098] The electrolyte may further include a nitric acid or nitrite-based compound as an additive in addition to the electrolyte salt and the organic solvent. The nitric acid or nitrite-based compound forms a stable film on the lithium metal electrode, which is the negative electrode, and has the effect of improving charge / discharge efficiency.
[0099] The nitric acid or nitrite compound is not particularly limited in the present invention, but may be one selected from the group consisting of inorganic nitric acid or nitrite compounds such as lithium nitrate (LiNO3), potassium nitrate (KNO3), cesium nitrate (CsNO3), barium nitrate (Ba(NO3)2), ammonium nitrate (NH4NO3), lithium nitrite (LiNO2), potassium nitrite (KNO2), cesium nitrite (CsNO2), and ammonium nitrite (NH4NO2); organic nitric acid or nitrite compounds such as methyl nitrate, dialkylimidazolium nitrate, guanidine nitrate, imidazolium nitrate, pyridinium nitrate, ethyl nitrate, propyl nitrate, butyl nitrate, pentyl nitrate, and octyl nitrate; and organic nitro compounds such as nitromethane, nitropropane, nitrobutane, nitrobenzene, dinitrobenzene, nitropyridine, dinitropyridine, nitrotoluene, and dinitrotoluene, and combinations thereof. Preferably, lithium nitrate is used.
[0100] The electrolyte may be injected at an appropriate step during the manufacturing process of the electrochemical device depending on the manufacturing process and required properties of the final product, i.e., before assembly of the electrochemical device or at the final step of assembly of the electrochemical device.
[0101] The lithium secondary battery according to the present invention can be manufactured by a lamination, stack and folding process of the separator and the electrodes in addition to a general winding process.
[0102] The shape of the lithium secondary battery is not particularly limited, and may be in various shapes such as a cylindrical shape, a laminated shape, a coin shape, or the like.
[0103] Preferred examples are described below to aid in understanding the present invention. However, the following examples are merely illustrative of the present invention, and it will be apparent to those skilled in the art that various changes and modifications are possible within the scope of the scope and technical ideas of the present invention. Naturally, such changes and modifications fall within the scope of the appended claims.
[0104] Examples 1 to 5. Preparation of positive electrodes for lithium-sulfur batteries Carbon nanotubes were injected into a centrifugal grinder (Netzsch, CSM) to produce carbon nanotubes with a particle size (D10 standard) of less than 10 μm. The carbon nanotubes and sulfur (Sigma-Aldrich product) were mixed and then heat-treated at 155° C. for 30 minutes to produce a sulfur-carbon composite (S:CNT=70:30).
[0105] The sulfur-carbon composite and the binder were mixed in a weight ratio of 96:4, and then added to DI water as a solvent to prepare a positive electrode slurry.
[0106] The positive electrode slurry was coated on a 20 μm thick aluminum foil current collector and then dried at 80° C. for 2 hours to prepare a positive electrode for a lithium-sulfur battery.
[0107] In Examples 1 to 5, the carbon nanotubes were pulverized by varying the rpm and linear velocity of the centrifugal pulverization. The rpm, linear velocity, particle size of the carbon nanotubes (based on D10), porosity of the positive electrode, and tap density of the carbon nanotubes are shown in Table 1 below.
[0108] [Table 1]
[0109] The carbon nanotubes of Examples 1 to 5 contain fine powder having a particle size (D10 standard) of less than 10 μm, and have a tap density of 0.01 to 0.1 g / cc. Even with the fine powder, the positive electrode has a porosity of more than 75%.
[0110] Comparative Examples 1 to 3. Production of Positive Electrodes for Lithium-Sulfur Batteries Carbon nanotubes and sulfur (Sigma-Aldrich product) were mixed and then heat-treated at 155°C for 30 minutes to produce a sulfur-carbon composite (S:CNT = 70:30).
[0111] The sulfur-carbon composite and the binder were mixed in a weight ratio of 96:4, and then added to DI water as a solvent to prepare a positive electrode slurry.
[0112] The positive electrode slurry was coated on a 20 μm thick aluminum foil current collector and then dried at 80° C. for 2 hours to prepare a positive electrode for a lithium-sulfur battery.
[0113] In Comparative Examples 1 to 3, the carbon nanotubes were not centrifugally crushed, and positive electrodes for lithium-sulfur batteries were manufactured using carbon nanotubes having different particle sizes (D10 standard). The particle sizes (D10 standard) of the carbon nanotubes and the porosity of the positive electrodes are shown in Table 2 below.
[0114] [Table 2]
[0115] In Comparative Example 1, the particle size (D10 standard) of the carbon nanotubes was more than 10 μm, and the porosity of the positive electrode was more than 75%, but the tap density was more than 0.1 g / cc.
[0116] In Comparative Examples 2 and 3, the particle size (D10 standard) of the carbon nanotubes was fine powder of less than 10 μm, and the fine powder blocked the pores of the positive electrode, resulting in a positive electrode with a porosity of 75% or less and a tap density of more than 0.1 g / cc.
[0117] Experimental Example 1. Measurement of discharge capacity and relative energy density of lithium-sulfur battery The positive electrodes of Examples 1 to 5 and Comparative Examples 1 to 3 were used to manufacture lithium-sulfur batteries.
[0118] Specifically, the positive electrode and the negative electrode were placed facing each other, a porous polyethylene was interposed between them as a separator, and an electrolyte was then injected to prepare a lithium-sulfur battery.
[0119] In this case, lithium metal was used as the negative electrode, and a mixture of 1M LiTFSI and 3% by weight lithium nitrate (LiNO3) dissolved in an organic solvent consisting of 2-methylfuran and dimethoxyethane (33:77 (volume ratio)) was used as the electrolyte.
[0120] Each of the lithium-sulfur batteries of Examples 1 to 5 and Comparative Examples 1 to 3 was discharged at a constant current of 0.5 C in CC mode at 25° C. until the voltage reached 1.8 V, and then charged at a constant current of 0.2 C until the voltage reached 2.5 V, and the discharge capacity was measured.
[0121] In addition, the relative energy density of each of the lithium-sulfur batteries of Examples 1 to 5 and Comparative Examples 1 to 3 was measured, and the discharge capacity and relative energy density are shown in the following Table 3. The relative energy density was calculated based on Comparative Example 2.
[0122] [Table 3]
[0123] From the results in Table 3, when taking Comparative Example 1 in which the particle size (D10 standard) of the carbon nanotubes exceeds 10 μm as a reference, Examples 1 to 5 of the present invention are capable of manufacturing positive electrodes with a low tap density of 0.01 to 0.1 g / cc and a porosity exceeding 75%, even though the particle size (D10 standard) of the carbon nanotubes is less than 10 μm, and as a result, discharge capacity and relative energy density were equivalent to or superior to those of Comparative Example 1.
[0124] In Comparative Examples 2 and 3, the particle size (D10 standard) of the carbon nanotubes was less than 10 μm, but because centrifugal pulverization was not performed, it was not possible to manufacture a positive electrode with a tap density exceeding 0.1 g / cc and a porosity exceeding 75%, and therefore the discharge capacity and relative energy density were very low.
[0125] Therefore, it can be seen that when the porous carbon material is centrifuged, the porosity of the positive electrode can be ensured even if the particle size (D10 standard) of the porous carbon material is less than 10 μm, and the discharge capacity and relative energy density of the lithium-sulfur battery can be improved.
Claims
1. A current collector; and a positive electrode active material layer disposed on at least one surface of the current collector; the positive electrode active material layer includes, as a positive electrode active material, a porous carbon material and a sulfur-carbon composite containing sulfur in at least a part of the inside and the outside surface of the porous carbon material; The particle size (D10 standard) of the porous carbon material is less than 10 μm; The positive electrode for a lithium-sulfur battery, wherein the porosity of the positive electrode is greater than 75% and less than or equal to 85%.
2. 2. The positive electrode for a lithium-sulfur battery according to claim 1, wherein the sulfur is contained in an amount of 65 to 80% by weight based on the total weight of the positive electrode active material layer.
3. 2. The positive electrode for a lithium-sulfur battery according to claim 1, wherein the tap density of the porous carbon material is 0.01 to 0.1 g / cc.
4. 2. The positive electrode for a lithium-sulfur battery according to claim 1, wherein the positive electrode active material layer further contains a binder or a conductive material.
5. (1) centrifugal crushing a porous carbon material to produce a porous carbon material having a particle size (D10 standard) of less than 10 μm; (2) mixing the porous carbon material with sulfur and heat treating the mixture to prepare a sulfur-carbon composite; (3) preparing a positive electrode slurry containing the sulfur-carbon composite; and (4) applying the positive electrode slurry to a current collector.
6. The method for producing a positive electrode for a lithium-sulfur battery according to claim 5, wherein the (1) step is centrifugal pulverization at 6000 to 18000 rpm and a linear velocity of 80 to 200 m / s.
7. The method for producing a positive electrode for a lithium-sulfur battery according to claim 5, wherein the porosity of the positive electrode is more than 75% and not more than 85%.
8. A lithium-sulfur battery comprising: the positive electrode according to any one of claims 1 to 4; a negative electrode; a separator interposed between the positive electrode and the negative electrode; and an electrolyte.
Citation Information
Patent Citations
High-energy-density lithium ion battery
CN111384388A
Online marketing advertising system with a variety of content marketing productions and how to control them
KR1020220028628A
Positive Electrode for Lithium Secondary Battery and Lithium Secondary Battery Comprising the Same
KR1020200109861A